Malaysian Challenges - Tierney, William; Sirat, M. (International Higher Education, 2008)
Malaysian tertiary education is a microcosm of the trends and challenges facing all of postsecondary education throughout the world. Privatization is increasing in the public sector. New providers have entered the Malaysian tertiary market. International rankings are a preoccupation of the government and research universities. The cost of education concerns parents, students, and the government. Whether the Ministry of Higher Education should continue to “steer from a distance” the nation's public postsecondary institutions or develop a more decentralized plan is being debated. How to stop the brain drain of talented Malaysian faculty, capitalize on the brain gain, serve the rising number of students who desire a postsecondary education, and provide jobs for an increasingly educated citizenry are issues being debated actively in the press and on the streets.